Penggunaan Media Sosial (Instagram) dalam Promosi Kesehatan Gigi dan Mulut terhadap Peningkatan Pengetahuan pada Pasien Usia Sekolah tentang Kesehatan Gigi dan Mulut di Puskesmas Minasa Upa - Hasrini Hasrini; Pariati Pariati; Zulkarnain Zulkarnain; Amirah Maritsa; Zahrawi Astrie Ahkam (Universitas Muhamadiyah Manado, 2022)
Knowledge of how to maintain proper dental health will greatly Affects theincidence of dental caries, brushing and rinsing teeth - gargling is one of the behaviors to maintain oral hygiene. behavior based on correct knowledge will last longer than behavior that is not based on knowledge, an effort to increase knowledge is through health education. Online media is one of the educational media to increase knowledge of dental and oral health. The type of research in this study is a comparative analysis or